Cell‐by‐cell quantification of the androgen receptor in benign and malignant prostate leads to a better understanding of changes linked to cancer initiation and progression - Seta Derderian; Tarik Benidir; Eleonora Scarlata; Turki Altaylouni; Lucie Hamel; Fatima Zahra Zouanat; Fadi Brimo; Armen Aprikian; Simone Chevalier (Wiley, 2023)
Abstract The androgen receptor (AR) plays a crucial role in the development and homeostasis of the prostate and is a key therapeutic target in prostate cancer (PCa). The gold standard therapy for advanced PCa is androgen deprivation therapy (ADT), which targets androgen production and AR signaling. However, resistance to ADT develops via AR‐dependent and AR‐independent mechanisms. As reports on AR expression patterns in PCa have been conflicting, we performed cell‐by‐cell AR quantification by immunohistochemistry in the benign and malignant prostate to monitor changes with disease development, progression, and hormonal treatment. Prostates from radical prostatectomy (RP) cases, both hormone‐naïve and hormone‐treated, prostate tissues from patients on palliative ADT, and bone metastases were included. In the normal prostate, AR is expressed in >99% of luminal cells, 51% of basal cells, and 61% of fibroblasts. An increase in the percentage of AR negative (%AR−) cancer cells along with a gradual loss of fibroblastic AR were observed with increasing Gleason grade and hormonal treatment. This was accompanied by a parallel increase in staining intensity of AR positive (AR+) cells under ADT. Staining AR with N‐ and C‐terminal antibodies yielded similar results. The combination of %AR− cancer cells, %AR− fibroblasts, and AR intensity score led to the definition of an AR index, which was predictive of biochemical recurrence in the RP cohort and further stratified patients of intermediate risk. Lastly, androgen receptor variant 7 (ARV7)+ cells and AR− cells expressing neuroendocrine and stem markers were interspersed among a majority of AR+ cells in ADT cases. Altogether, the comprehensive quantification of AR expression in the prostate reveals concomitant changes in tumor cell subtypes and fibroblasts, emphasizing the significance of AR− cells with disease progression and palliative ADT.